(untitled) (Nepal Medical College Journal, 2025)
Properly completed Computed Tomography (CT) requisition forms are essential for accurate imaging, timely diagnosis, and patient safety. Incomplete documentation may lead to delays, errors, and potential harm. This audit evaluated the completeness of CT requisition forms at Nepal Medical College Teaching Hospital. A cross-sectional audit of 267 CT requisition forms was performed. Data on patient demographics, clinical information, and administrative details were collected and analyzed against established standards. Descriptive statistics were used to quantify completeness. Patient name and age were recorded in 99.3% and 98.9% of forms, respectively, while 97.4% documented patient sex. Hospital numbers were missing in 50.2%, provisional diagnosis in 59.6%, and the referring department in 77.9%. Doctor signatures were absent in 29.2%, and allergy history was omitted in 92.5%. Only 7.5% of the forms were fully complete. The audit revealed considerable gaps in the completion of CT requisition forms. Targeted interventions, staff training, and periodic re-audits are recommended to enhance documentation quality and patient safety.